MANAGERIAL POLEMIC OF FOUNDATIONS IN THE ISLAMIC BOARDING SCHOOL AND DORMITORY EDUCATION SYSTEM - Maulidah, Nurur Rifqotul; Zaini, Abdul Wahid; Jaannah, Ulfa Qomariatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Foundation management is fundamental in successfully managing religious-based educational institutions, such as Islamic boarding schools and modern dormitories. This study compares the managerial systems of two academic institutions, namely the Islamic Boarding School of Syafi'iyah and the Integrated Insan the Dormitory, which have different approaches but the same goal: to form superior individuals in academic, spiritual, and moral aspects. The Islamic Boarding School of Syafi'iyah uses a traditional model based on classical Islamic values with centralized decision-making. At the same time, the Integrated Insan Dormitory adopts modern management based on participation with a more professional organizational structure. These differences include decision-making patterns, human resource management, and approaches to character education. This study aims to identify the advantages and challenges of both managerial approaches and offer solutions to overcome the polemics in the management of educational foundations. This study is expected to provide new insights for educational foundation managers in developing effective managerial systems to meet the needs of their respective institutions.